2019
DOI: 10.1039/c9cp02363a
|View full text |Cite
|
Sign up to set email alerts
|

Optical band gap of cross-linked, curved, and radical polyaromatic hydrocarbons

Abstract: The impact of cross-linking, curvature, and radical character on the optical band gap of polyaromatic hydrocarbons has been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 64 publications
3
37
0
Order By: Relevance
“…Optical band gap theory suggests that we may consider absorption of the refractory particle components to be determined by the size of polycyclic aromatic units (Menon et al 2019). The relationship found between AAE and fringe length (Figure 5a), and AAE and ( Figure 6) support that the light absorption wavelength dependence of soot depends on the size of refractory aromatic units in the soot particle.…”
Section: Optical Band Gap and Refractory Sp-ams Analysismentioning
confidence: 75%
See 3 more Smart Citations
“…Optical band gap theory suggests that we may consider absorption of the refractory particle components to be determined by the size of polycyclic aromatic units (Menon et al 2019). The relationship found between AAE and fringe length (Figure 5a), and AAE and ( Figure 6) support that the light absorption wavelength dependence of soot depends on the size of refractory aromatic units in the soot particle.…”
Section: Optical Band Gap and Refractory Sp-ams Analysismentioning
confidence: 75%
“…The absorption measurements at seven wavelengths allowed us to evaluate AAEs in different wavelength intervals. The high optical band gap energies (Menon et al 2019) and absorption spectra (Huisken et al 2013) associated with non-refractory PAHs observed in the AMS (mainly PAHs with molecular masses of 202-300 Da) suggested that the non-refractory components that were removed in the TD would have only a minor contribution to absorption at wavelengths longer than 660 nm. Therefore, AAEs were evaluated in two wavelength intervals: the full 370-950 nm wavelength interval (AAE 370-950nm ) and for the 660-950 nm wavelength interval (AAE 660-950nm ).…”
Section: Aae In Different Wavelength Intervalsmentioning
confidence: 99%
See 2 more Smart Citations
“…64 The UVvisible electronic transitions in sp 2 carbon systems such as PAHs rely on π * -π transitions. 65 Several studies show that there is an inverse power law relationship between optical band gap (OBG) and the number of benzene rings in PAHs 66,67 . An increase in MW of PAHs broadens their absorption bands towards longer wavelengths and red-shifts their emission bands due to the decreasing OBG.…”
Section: Spectral Information From Eem Analysismentioning
confidence: 99%